Job satisfaction and organizational commitment: An empirical investigation among ICT-SMEs. - Valaei, Naser *; Rezaei, Sajad (Emerald, 2016)
Purpose – The aim of this study is to examine the structural relationship between Spector’s nine job satisfaction facets (supervision, nature of the work, communication, contingent rewards, co-worker, fringe benefits, payment, promotion and operating procedures), organizational commitment facets (normative commitment, affective commitment and continuance commitment) and the influence of employees’ years of experience on satisfaction and commitment relationships. Owing to the nature of the industry, employee satisfaction, retention and commitment in Information and Communications Technology-Small and Medium-sized Enterprise (ICT-SME) is a matter of great concern. Design/methodology/approach – A total of 256 valid questionnaires were collected among employees of Information and Communications Technology-Small and Medium-sized Enterprises (ICT-SMEs) to evaluate the measurement and structural model using partial least squares path modelling approach. Findings – The findings indicate that payment, promotion, fringe benefits, co-worker, communication, operating procedures and nature of the work are positively associated with affective commitment. Furthermore, payment, promotion, fringe benefits, supervision, contingent rewards, operating procedures and nature of the work have a positive relationship with normative commitment. Considering employees’ years of experience as a categorical moderating variable, the results of partial least squares multi-group analysis show how the discrepancies between employees’ years of experience influence their level of commitment. Originality/value – This study reveals that employees’ affective and normative commitments are positively associated and their continuance commitment is contingent upon their affective commitment, and not normative commitment. There are only three factors, i.e. promotion, fringe benefits and operating procedures, that are conductive to employees’ continuance commitment. Contributions, implications and limitations of the study are discussed.